Parâmetros de ajustes dos modelos de desenvolvimento foliar de cana-de-açúcar - Hanauer, Joana Graciela (2014)
The objectives of this thesis were (i) to identify the expanded leaves number (LNexp) and tips (LNtip) from which there is reduction in the contribution of culm reserves to leaf appearance rate in sugarcane and (ii) the effect of different densities of stem in leaf development in the culture of sugarcane. The experiments were conducted at the experimental area of the Departamento de Fitotecnia, Centro de Ciências Rurais, Universidade Federal de Santa Maria, during the 2012/2013 growing season. The sugarcane clone used was SP 711406, with intermediate developmental cycle and well adapted to this location. To achieve the first objective, described in Chapter 1, the experimental design was randomized with 32 replications. Treatments were culm cuttings with: twice the length of the internode, one internode, half the length of internodes, and no internode. Results indicated that the reserves of the culm cuttings of sugarcane have their maximum contribution to the emission of the first two expanded leaves and of the first five leaf tips, and the appearance rate of subsequent leaves decrease due to reduction in culm cuttings reserves. To achieve the second objective, described in Chapter 2, the experiment was conducted in plant cane cultivation system. In plants marked the variables expanded leaves number (LNexp) and tips leaves number (LNtip) in the main stem, linear dimensions of expanded leaves and later, at harvest were determined yield components (total stem length were measured, fresh biomass of commercial stem dry mass commercial stem, number of nodes, number of internodes, internode length, fresh weight and dry weight of internode). It was concluded that the change in rate of leaf emergence (phyllochron greater) from the 15th leaf on is caused by a change in microclimate in the canopy and the increase of the sink strength of photosynthates to stem growth; and yield components are affected negatively by lower densities than those recommended for the crop planting.